A study on the effects of social networking sites towards academic performance: an investigation of pattern of usage and students' perception / Nur Aida Mastura Muhd Ali, Puteri Nur Arishah Megat Muzaffar Shah and Raihan Ibrahim - Muhd Ali, Nur Aida Mastura; Megat Muzaffar Shah, Puteri Nur Arishah; Ibrahim, Raihan (2019)
Social networking sites have been transformed from a few user based sites to the global phenomenon within last one decade. Thus, the popularity of the social networking sites at the large scale among the students create concerns of the parents and academic institutes as majority as of the students are using social networking sites for entertainment purpose like chatting with friends, online games, online shopping and others. Due to that, this study attempts to study these two objectives, which are; (1) to describe the pattern of social networking sites, (2) to examine the effect of students' perception and usage of social networking sites towards academic performance. The data were collected using a questionnaire from 425 degree students from UiTM Negeri Sembilan Campus Seremban 3. Descriptive analysis was performed in order to achieve the first objective. It is found that the students often engage with other students on academic related activities using social networking sites. Besides that, 64.2% of the respondents also use both, the mobile device and laptop to access the social networking sites and 43 .1 % spends more than 5 hours on social networking sites per day. Multiple Linear Regression (MLR) analysis were also performed in this research in order to achieve objective (2). Based on the analysis, only one variable is significant which is Perception. However, the result cannot be generalized on the population as non¬-probability sampling was also involved in this study.